Constructing Knowledge is More Complex: Opposing the Uncritical Adoption of Pop Psychological Fads and Neuromyths in Education among teachers in private schools in Midrand, South Africa - Jacob, Lizanne Leslie (University of the Witwatersrand, Johannesburg, 2025)
This study examined the rise of pop psychological fads and neuromyths within education, which are false or misleading beliefs that lack scientific validation but are widely adopted. Pop psychology often offers quick solutions to complex problems, while neuromyths—misunderstandings about brain function—have become prevalent in educational practices. Teachers may also resort to these unproven concepts due to a lack of understanding of the complexities of learning, leading to ineffective teaching strategies. Although these beliefs may seem appealing, they can waste resources and time, and their uncritical adoption in classrooms can hinder evidence-based teaching methods and ultimately harm student learning outcomes. The study highlights the importance of moving beyond these myths to embrace more scientifically supported approaches in education. However, there is dearth of literature in South African context regarding adoption of neuromyths and fads among teachers, and this is the research gap that was filled by this PhD study. This study aimed to investigate adoption of Pop Psychological Fads and Neuromyths in Education among teachers in private schools in Midrand, South Africa. The study was informed by two theories, Feuerstein’s Mediated Learning Experience Theory and the Constructivist Learning Theory. Within an interpretivist paradigm, the study adopted a qualitative research methodology, and a multiple case study design was utilized. Data was collected from four private schools in Midrand, Gauteng, South Africa. The study sample size comprised 20 trained professional teachers from four private schools in Midrand, South Africa, with five teachers selected from each school. The teachers were chosen using purposive sampling method. Semi-structured interviews were used as tools to gather data. The four criteria—credibility, dependability, confirmability, and transferability—ensured the reliability and validity of qualitative data. Thematic framework was used to analyse the qualitative data from interviews. The study findings indicated that many teachers, despite being aware of prevalent neuromyths like the left brain-right brain myth and learning styles, continue to incorporate these misconceptions into their teaching practices. The findings also reported that teachers gather knowledge from a range of sources, including professional development, media, and peer discussions, but often fail to critically evaluate the credibility of this information. Thus, many teachers believe in fads and neuromyths about learning and brain function, despite evidence against this. The findings also indicated that teachers acquired these fads from sources like professional development seminars and media. The study concluded that misinformation-based strategies often do not improve learning outcomes compared to scientifically validated methods, emphasizing the importance of critical thinking and evidence-based decision-making. The study further concluded that many teachers, despite being aware of prevalent neuromyths, still incorporate these misconceptions into their teaching, often due to a lack of critical evaluation of the sources of information they encounter. The study findings have led to the development of framework for continuous professional development to help address misconceptions from neuromyths and fads, which aims to help teachers critically assess and eliminate unscientific practices, fostering a culture of evidence-based teaching to improve student outcomes.
A thesis submitted for the fulfilment of the requirements of the degree of Doctor of Philosophy in Education, to the Faculty of Humanities, Wits School of Education, at the University of the Witwatersrand, Johannesburg, 2025
Keywords: Educational fads; Educational policies; Neuromyths; Professional development; Teacher belief.; UCTD; SDG-4: Quality education; SDG-10: Reduced inequalities